HUBUNGAN ANTARA STRATEGI COPING TERHADAP PERILAKU KEKERASAN PADA SINGLE PARENT (IBU) DI KECAMATAN PEKANBARU KOTA PEKANBARU - Risma Agtia Choserine; Ria Novianti; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research has a purpose to know about the relation between coping strategy in violent behaviour by single parent in Pekanbaru Subdistrict, Pekanbaru City. Kind of this reasearch is correlation. Sampling tool used random sample and the result set of this research is 60 single parent. The collecting data in this research are primer data and used questionnaire or closed statement questionnaire. The result of this research found violent behaviour by single parent (mother) in Subdistrict Pekanbaru, Pekanbaru city in medium category, that 23.46 %. Based on corellation coefficient value above, P value = 342 showed that single parent (mother) was high. The result of determinant coefficient is 11.69 % to violent behaviour by single parent (mother). From the result, it can be happened because mother’s emotional stress was uncontrolled caused bay any problem they faceKeyword: Violent, Behavior , Coping Strategy